The Nexus among Agriculture Sector Development and Environmental Degradation in Emerging Economies - Buket Altınöz (ETIKONOMI, 2022)
This paper aims to determine the effect of agriculture sectordevelopment on CO2 emissions in 10 big emerging marketeconomies. This relationship is tested for the first time for emergingeconomies by using the panel quantile regression approach. Theresults suggest that agricultural value-added mitigate emissionsin lower, middle-lower, and upper quantile levels. This resultimplies that the agricultural sector is an effective policy toolin reducing pollution in these countries. Economic growth andnatural resources rent have a positive impact on pollution. Financialdevelopment only has an emission-reducing effect at the middleupperquantile level, while globalization has a negative impact onCO2 emissions both in the middle-upper and upper quantiles.These results justify the consideration of heterogeneous effects andallow clear policy implications. Moreover, the critical importanceof agricultural policies for environmental quality in these countriesis emphasized with concrete evidence.JEL Classification: O13, Q56, C33